Psychosocial risk factors outside in university administrative personnel - Romero-Díaz, Carmen Helena (2016)
Introduction. This study aimed to characterize the psychosocial risk by outside working factors of administrative staff of the University Corporation of the Coast - CUC and the determination of their level of stress.Method. From a census was determined the population, which was formed by 227 workers. It is a research, descriptive, transactional with non-experimental design. The collection of information used instruments for the evaluation of factors of psychosocial risks, that it is regulations of the Ministry of Social protection of Colombia.Results. It showed the main factors of this type of risk, as well as your stress level, present in the administrative employees of the institution, showing that 68 workers joined in the categories high and high stress levels, 76 subjects were grouped by levels the medium and low, while the remaining 83, had very low risk.Conclusion. Firstly, prevailed the risk factor about "transportation of home - work - home", the second factor "Economic situation of the family group", and thirdly the "characteristics of the dwelling and its surroundings". There is a considerable alarm for the maintenance of the good health of the administrative staff of the University, when the levels stress are in the category of stress low and it need should undertake special interventions and with the rising from the middle level undertake epidemiological values of the nation's public health.